Study on the irrigation uniformity of impact sprinkler under low pressure with and without aeration - Qureshi, Waqar Ahmed; Xiang, Qingjiang; Xu, Zhengdian; Fan, Zhizun (Frontiers in Energy Research, 2023)
The distribution of water deteriorates when the operating pressure of an impact sprinkler (IS) decreases to some level. The aeration jet method is utilized to form an aeration impact sprinkler (AIS), aiming to improve the uniformity of water distribution under low pressure. Based on the structures of a 20PY2 impact sprinkler, an IS and AIS with the same sprinkler discharge were studied under operating pressures range between 150 and 250 kPa. A square test zone was formed by the four sprinklers, and the combined irrigation experiment was conducted under windless conditions. The results showed that the water loss ranged from 3 % to 9.5 % in all 18 test schemes. The coefficient of uniformity (CU) and distribution uniformity (DU) were used to quantify the degree of uniformity. The AIS had an approximately 3 % to 7 % greater CU than the IS, which resulted in the CU reaching the specified value in the IS standard when the sprinkler functioned under low operating pressure. A linear relationship was found between the CU and DUlq. The uniformity of water distribution clearly changed with the operating pressure (150 kPa, 200 kPa, and 250 kPa) but decreased slightly with the increase in combination spacing (1 R, 1.1 R, and 1.2 R). In addition, the results of field experiment were compared with those of the simulation developed from a single sprinkler indoor experiment based on the water distribution radial curve. The simulated coefficient of uniformity was highly consistent with the experimental data and had an error of < 7 %. A sprinkler water jet with the aeration method was proven to be a feasible solution to reduce the operating pressure.